Upaya Meningkatan Motivasi Belajar Siswa Melalui Layanan Bimbingan Kelompok di Kelas XII-IIS-1 SMA Negeri 1 Pujut - Baiq Serikandi (Universitas Pendidikan Mandalika, 2020)
This study aims to increase student motivation through group counseling services in class XII-IIS-1 SMA Negeri 1 Pujut. This research method uses Guidance and Counseling Action Research (PTBK). Based on the results of research and discussion of the results of analysis of teacher observation data, student activities and the results of the evaluation of group motivation services learning motivation cycle I and cycle II can be concluded as follows. In cycle I the activities of the teacher as many as 13 are categorized as good, because it is located at an interval of 11 ≤ Ag <15. While the score of the teacher's activity group guidance activities in the second cycle of 14, can be categorized as good, because it is located at an interval of 11 ≤ Ag <15. While the activities students in group guidance activities in the first cycle of 52, obtained from the total score on each indicator. Based on the criteria for student activity, student activity in cycle I can be categorized active, because it is located at an interval of 41 ≤ As <60. While student activity in cycle II of 53 can be categorized very active, because it is located at an interval of 41 ≤ As <60. Based on the results of data analysis the implementation of actions in the first cycle showed that the percentage of learning motivation was 20%, low by 40% and learning motivation in the very low category of 40%. While based on the results of the analysis of the second cycle obtained students have very high learning motivation of 10%, high by 50% and moderate learning motivation by 10% and low by 10%, so based on the results of the second cycle has reached the indicators of success of the research that has been set.